Oxysterols as markers of neurological disease - a review - Leoni, Valerio (Scandinavian journal of clinical and laboratory investigation, 2009)
Cholesterol plays a crucial structural role in the brain and local synthesis covers almost all the requirements of the brain. To maintain homeostasis, the excess of cholesterol is converted into the more hydrophilic oxysterol 24S-hydroxycholesterol by the neuron-specific enzyme CYP46A1. About 99 % of the total excretion of this oxysterol by the brain occurs across the blood-brain barrier directly into the bloodstream. Almost all the 24S-hydroxycholesterol present in human circulation has a cerebral origin and its concentrations depend on the number of metabolically active neurons located in the grey matter of the brain. Neurodegeneration, with loss of neurons, and the subsequent brain atrophy are associated with significantly reduced concentrations of oxysterols. 24S-Hydroxycholesterol can thus be used as a surrogate marker of brain atrophy in neurodegenerative diseases such as Alzheimer and multiple sclerosis. Less than 1 % of the total excretion of 24S-hydroxycholesterol is via the cerebrospinal fluid. This small fraction appears to reflect neuronal damage and rate of neuronal loss rather than the total number of metabolically active neuronal cells. Patients with neurodegenerative disorders have thus been found to have increased concentrations of 24S-hydroxycholesterol in cerebrospinal fluid, in parallel with decreased concentrations in the circulation. Compared with other available biomarkers in CSF, such as Total Tau, Phospo-Tau and 42 amyloid, the 24S-hydroxycholesterol appears to be the most sensitive biomarker in the evaluation of patients with cognitive impairment disease.